Recent Advances in Lifetime and Reliability Models - Cordeiro, Gauss M. (Bentham Science Publishers, 2020)
Mathematicians and statisticians have made significant academic progress on the subject of distribution theory in the last two decades, and this area of study is becoming one of the main statistical tools for the analysis of lifetime (survival) data. In many ways, lifetime distributions are the common language of survival dialogue because the framework subsumes many statistical properties of interest, such as reliability, entropy and maximum likelihood. Recent Advances in Lifetime and Reliability Models provides a comprehensive account of models and methods for lifetime models. Building from p.